2021
DOI: 10.1208/s12249-020-01880-0
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Injection Performance in Yucatan Miniature Pigs with and without Human Hyaluronidase and Auto-injector Tolerability in Humans

Abstract: Recombinant human hyaluronidase PH20 (rHuPH20) facilitates subcutaneous (SC) delivery of co-administered therapeutic agents by locally and transiently degrading hyaluronan in the SC space, and can be administered with therapeutics using a variety of devices. Two SC delivery studies were carried out to assess auto-injector (AI) performance, each in 18 Yucatan miniature pigs. Abdominal injections were administered using three auto-injectors of 1 mL (AI1) and 2 mL (AI2 and sAI2) with different injection speeds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…These results suggest that rHuPH20 can improve the performance of delivery devices by degrading HA in the extracellular matrix of the SC space, reducing the SC tissue constraints to bulk fluid flow that otherwise impede the device hardware, thereby allowing for higher delivery rates required for large-volume SC administration (Bookbinder et al., 2006 ; Kang et al., 2012 ). Similar results were observed in a recent study of miniature pigs, in which the addition of rHuPH20 to test solutions administered subcutaneously resulted in shorter injection times and reduced swelling at the injection site with some auto-injector devices (Shi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggest that rHuPH20 can improve the performance of delivery devices by degrading HA in the extracellular matrix of the SC space, reducing the SC tissue constraints to bulk fluid flow that otherwise impede the device hardware, thereby allowing for higher delivery rates required for large-volume SC administration (Bookbinder et al., 2006 ; Kang et al., 2012 ). Similar results were observed in a recent study of miniature pigs, in which the addition of rHuPH20 to test solutions administered subcutaneously resulted in shorter injection times and reduced swelling at the injection site with some auto-injector devices (Shi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, previous pre-clinical studies have demonstrated that infusion of human Ig facilitated by rHuPH20 was effective in reducing HA in the SC space in a Yucatan miniature pig model (Kang et al., 2012 ). A previous study reported similarities between Yucatan miniature pigs and humans in terms of injection-site swelling and back leakage when test solutions were administered in the SC space (Shi et al., 2021 ). It has also been demonstrated that rHuPH20 can facilitate SC infusion of a polyclonal human gamma Ig solution in a Yucatan miniature pig model by significantly reducing in-line pressure, resulting in increased fluid dispersion while minimizing infusion-related local swelling and induration (Kang et al., 2012 ).…”
Section: Introductionmentioning
confidence: 95%
“…These devices improve the ease of administration for patients and caregivers over needle and syringe delivery systems. Preclinical studies have shown that the addition of rHuPH20 to a SC injection via an autoinjector resulted in improved SC injection performance compared with placebo for volumes up to 2 mL even at high delivery rates [94]. It is a reasonable hypothesis to suggest that similar results are likely to be seen when rHuPH20 is used in a device in a human study.…”
Section: Expert Opinionmentioning
confidence: 98%
“…The coadministration of hyaluronidase has been shown to not only increase bioavailability and reduce t max , but also to improve overall injection by lower swelling and reduced injection time due to the onset of action for hyaluronidase. 19,20 However, the onset is not rapid enough to enable the use of an autoinjector which typically injects the solution in under 15 seconds. 15…”
Section: Subcutaneous Injectionmentioning
confidence: 99%
“…The DAR in Polivy TM is 3.5, and in Padcev TM is 3.8. Polivy TM is a lyophilized powder and after reconstitution with 1.8 mL or 7.2 mL WFI contains 20 mg/mL polatuzumab vedotin-piiq, sucrose 40 mg/mL, polysorbate 20 (1 mg/mL), and a pH 5.3 succinate 0.008M buffer. Padcev TM is a lyophilized powder and after reconstitution with 2.3 mL or 3.3 mL WFI contains 10 mg/mL enfortumab vedotin-ejfv, trehalose dihydrate 55 mg/mL, polysorbate 20 (0.2 mg/mL), and a pH 6.0 histidine 0.02M buffer.…”
Section: Antibody Drug Conjugatesmentioning
confidence: 99%